ONE MAP POLICY: DIGITAL ADMINISTRATION METHODS AS AN EFFORT TO SOLVE LAND OVERLAPS IN INDONESIA - Pelengkahu, Muhammad Rahjay (Universitas Bengkulu, 2025)
Until now, Indonesia's land use problem has not fully found a bright spot. Moreover, this problem originated from a map made by the government itself. Therefore, holding the One Map Policy in the form of government policies to realize good land governance. This research aims to find out how effective the One Map Policy is in solving land problems and realizing good spatial governance to provide welfare to the people. This research is written using normative juridical methods using literature studies that examine a problem from a legal point of view and look for data with reading materials. According to the finding, one map policy was designed as a form of digital transformation in the field of public administration which refers to the strategy of synchronizing data information in one map at each institution or ministry. In its implementation, the one map policy has proven to be a modern alternative and an important policy in resolving overlapping land uses that occur in society.